2014
DOI: 10.1016/j.concog.2014.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Self-referential memory in autism spectrum disorder and typical development: Exploring the ownership effect

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
62
4
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(74 citation statements)
references
References 37 publications
(25 reference statements)
7
62
4
1
Order By: Relevance
“…Of particular relevance to early development, self‐processing issues may be an important element of autism. Studies of children (Gillespie‐Smith, Ballantyne, Branigan, Turk, & Cunningham, ; Henderson et al., ) and adults (Grisdale, Lind, Eacott, & Williams, ; Lombardo, Barnes, Wheelwright, & Baron‐Cohen, ; Toichi et al., ) with autism suggest there may be unusual SRE patterns, which may be symptomatic of disruptions in the SMS (see Lind & Bowler, ). Interestingly, brain imaging studies suggest that adolescents with and without autism show divergent patterns of neural activation when engaged in self‐processing (Pfeifer et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Of particular relevance to early development, self‐processing issues may be an important element of autism. Studies of children (Gillespie‐Smith, Ballantyne, Branigan, Turk, & Cunningham, ; Henderson et al., ) and adults (Grisdale, Lind, Eacott, & Williams, ; Lombardo, Barnes, Wheelwright, & Baron‐Cohen, ; Toichi et al., ) with autism suggest there may be unusual SRE patterns, which may be symptomatic of disruptions in the SMS (see Lind & Bowler, ). Interestingly, brain imaging studies suggest that adolescents with and without autism show divergent patterns of neural activation when engaged in self‐processing (Pfeifer et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Henderson et al found that the extent of this diminution was associated significantly with the severity of ASD features (more ASD traits = smaller SRE). Likewise, Grisdale, Lind, Eacott, and Williams [, Experiment 2] found that the ownership effect was significantly diminished in adults with ASD, relative to that observed in age‐, IQ‐, and sex‐matched comparison participants. Moreover, Grisdale et al (Exp.…”
Section: Introductionmentioning
confidence: 98%
“…There was a significant negative association between self‐advantage score and both measures of ASD trait severity (SCQ r = −.507, p = .016; ASDS scores r = −.608, p = .003). This suggests that the more autistic traits participants showed, the lower the self‐advantage, a pattern that replicates previous work (Grisdale et al ., ) but initially seems at odds with the heightened self‐advantage of participants in the ASD group in this study. Examination of memory for self‐owned and other‐owned items within the ASD group provides an explanation.…”
Section: Resultsmentioning
confidence: 55%
“…Indeed, the ASD group actually showed a higher SRE relative to the comparison groups. Although this is contrary to previous studies in which SRE has been lower in ASD compared to controls (Grisdale et al ., ; Henderson et al ., ), it is consistent with the abundance of ASD research suggesting that individuals with autism pay less attention to other people than neurotypical comparison groups (Hobson, ; Lord, Rutter, & Le Couteur, ; Werner, Dawson, Osterling, & Dinno, ). If there is egocentricity and reduced interest in others, and by extension, others’ belongings, then this should increase SREs by exacerbating the difference between attention paid to self‐ and other‐referent stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation